2016
DOI: 10.1097/ijg.0000000000000343
|View full text |Cite
|
Sign up to set email alerts
|

Early Glaucoma Screening Using the Ibopamine Provocative Test

Abstract: The ibopamine test showed an adequate diagnostic performance to detect individuals at increased risk of glaucoma in a very early stage of the disease. While further studies are required, the provocative ibopamine test for the diagnosis of early glaucoma is promissory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In a recent study on 44 patients and 37 controls, early glaucoma was diagnosed in 26 patients, and the sensitivity and specificity of the ibopamine test to identify patients with early glaucoma were 78.7% and 71.6%, [30]. At multivariable analyses, subjects with a positive ibopamine test at baseline had an 8-fold higher risk of glaucoma compared with those with a negative test.…”
Section: Provocative Testmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study on 44 patients and 37 controls, early glaucoma was diagnosed in 26 patients, and the sensitivity and specificity of the ibopamine test to identify patients with early glaucoma were 78.7% and 71.6%, [30]. At multivariable analyses, subjects with a positive ibopamine test at baseline had an 8-fold higher risk of glaucoma compared with those with a negative test.…”
Section: Provocative Testmentioning
confidence: 99%
“…It has been consistently shown that the instillation of ibopamine 2% results in a marked (up to 92%) increase of IOP in eyes with open-angle glaucoma, while no such effect is reported in healthy eyes [3,9,18,28,29,30]. This dose-dependent effect reaches its peak within 45 minutes from the first instillation and lasts about 180 minutes, without any painful symptom or ocular discomfort [18].…”
Section: Provocative Testmentioning
confidence: 99%
See 1 more Smart Citation